2013
DOI: 10.1111/mec.12349
|View full text |Cite
|
Sign up to set email alerts
|

MHC‐disassortative mate choice and inbreeding avoidance in a solitary primate

Abstract: Sexual selection theory suggests that choice for partners carrying dissimilar genes at the major histocompatibility complex (MHC) may play a role in maintaining genetic variation in animal populations by limiting inbreeding or improving the immunity of future offspring. However, it is often difficult to establish whether the observed MHC dissimilarity among mates drives mate choice or represents a by-product of inbreeding avoidance based on MHC-independent cues. Here, we used 454-sequencing and a 10-year study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 79 publications
(121 reference statements)
3
53
1
1
Order By: Relevance
“…Choosing partners with maximal or optimal genetic dissimilarity may help to avoid inbreeding or excessive outbreeding, respectively. To increase offspring diversity at key functional loci in a natural population, a recent study indicated that inbreeding avoidance was along with disassortative mate choice at DRB , but not at DQB locus [45]. Our results also seem to support this point.…”
Section: Discussionsupporting
confidence: 83%
“…Choosing partners with maximal or optimal genetic dissimilarity may help to avoid inbreeding or excessive outbreeding, respectively. To increase offspring diversity at key functional loci in a natural population, a recent study indicated that inbreeding avoidance was along with disassortative mate choice at DRB , but not at DQB locus [45]. Our results also seem to support this point.…”
Section: Discussionsupporting
confidence: 83%
“…5,89,96,99,134,137 Additionally, this relationship has been detected solely as female preference for males. Similar findings were detected by Kamiya et al Sauermann et al 137 Huchard et al 135 Huchard et al 135 Yang et al 139 Huchard et al 90 Setchell et al 89 Schwensow et al 5 …”
Section: Selection For Mates With Greater Mhc Diversitysupporting
confidence: 78%
“…Sauermann et al 137 Sauermann et al 137 Huchard et al 135 Yang 90 Setchell et al 89 Schwensow et al 5 Schwensow et al 5 Sauermann et al 137…”
Section: Mate Choice Preference Mate Choice Preferenceunclassified
See 1 more Smart Citation
“…In support of this assumption, a possible link between highly divergent or specific MHC genotypes and individual fitness (Schad et al 2005; Schwensow et al 2007, 2010a, b; Sommer et al 2014) and mate choice (Schwensow et al 2008a, b; Huchard et al 2013) has been suggested for two widely distributed lemurs— Microcebus murinus and Cheirogaleus medius (Cheirogaleidae, Primates). Consequently, the evaluation of MHC variation retained in populations of endangered confamiliar species can provide valuable insights to assess their viability.…”
Section: Introductionmentioning
confidence: 97%